Sagittal Craniosynostosis with Uncommon Anatomical Pathologies in a 56-Year-Old Male Cadaver. (8th December 2019) - Frolov, Andrey; Lawson, Craig; Olatunde, Joshua; Goodrich, James T.; Martin III, John R.
Abstract : Sagittal craniosynostosis (CS) is a pathologic condition that results in premature fusion of the sagittal suture, restricting the transverse growth of the skull leading in some cases to elevated intracranial pressure and neurodevelopmental delay. There is still much to be learned about the etiology of CS. Here, we report a case of 56-year-old male cadaver that we describe as sagittal CS with torus palatinus being an additional anomaly. The craniotomy was unsuccessful (cephalic index, CI = 56) and resulted in abnormal vertical outgrowth of the craniotomized bone strip. The histological analysis of the latter revealed atypical, noncompensatory massive bone overproduction. Exome sequencing of DNA extracted from the cadaveric tissue specimen performed on the Next Generation Sequencing (NGS) platform yielded 81 genetic variants identified as pathologic. Nine of those variants could be directly linked to CS with five of them targeting RhoA GTPase signaling, with a potential to make it sustained in nature. The latter could trigger upregulated calvarial osteogenesis leading to premature suture fusion, skull bone thickening, and craniotomized bone strip outgrowth observed in the present case.